Defending The Frontline: Infection Prevention And Stewardship Against Multidrug-Resistant Organisms (The Review of Diabetic Studies, 2024)
BackgroundMultidrug-resistant organisms (MDROs) pose a major threat to healthcare systems worldwide, causing increased morbidity, mortality, and economic costs, with rises in healthcare-associated (up to two-thirds) and community-acquired infections. Sentinel pathogens like MRSA, VRE, ESBL-Enterobacterales, CRE, and MDR Pseudomonas/Acinetobacter drive invasive infections, particularly in ICUs where mortality exceeds 35-40%.​MethodsThis narrative review synthesizes evidence from global epidemiologic studies, systematic reviews, meta-analyses, and surveillance data on MDRO burden, transmission, infection prevention/control (IPC), antimicrobial stewardship (ASP), and emerging strategies across ICU, non-ICU, community, and special settings.​ResultsMDROs show high colonization (10-60%), elevated mortality (20-50%), prolonged stays, and costs (e.g., $1.9 billion/year). Horizontal IPC (hand hygiene, bundles) and ASP (de-escalation, rapid diagnostics) reduce incidence by 15-50%; universal decolonization cuts MRSA by 37%; barriers persist in LMICs.​ConclusionsStrengthening integrated AID stewardship, One Health approaches, and novel diagnostics/therapeutics is essential to bolster MDRO defenses; future RCTs and implementation science are needed for resilient strategies.​